2020
DOI: 10.1097/mao.0000000000003003
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Recurrent Cholesteatoma in Rural Versus Urban Populations

Abstract: Objective: Chronic ear disease presents a unique challenge to otolaryngologists in both rural and urban settings. Cholesteatoma remains a difficult disease to treat in rural populations due to limited healthcare access and high risk of recurrence. The purpose of this study was to determine if there are differences in surgical outcomes among patients with acquired cholesteatoma residing in rural versus urban settings. Study Design: Single-surgeon retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Four studies pertained to otologic conditions other than hearing loss. Kennedy et al 51 found that rural patients are more likely to have residual cholesteatomas postoperatively. Crowson et al 52 found ototopical antibiotics are prescribed by the same proportion of ear, nose, and throat (ENT) vs non‐ENT prescribers in both rural and urban settings.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies pertained to otologic conditions other than hearing loss. Kennedy et al 51 found that rural patients are more likely to have residual cholesteatomas postoperatively. Crowson et al 52 found ototopical antibiotics are prescribed by the same proportion of ear, nose, and throat (ENT) vs non‐ENT prescribers in both rural and urban settings.…”
Section: Resultsmentioning
confidence: 99%
“…Tinnitus was studied in 1 article with race/ethnicity as the disparity category (n = 1) and its risk factors in African Americans in particular 48 . Vertigo/dizziness and cholesteatoma were each associated with an article under the geographic/urban‐rural category 49 , 50 . Cholesteatoma was also associated with a comprehensive disparity article that discussed the relationship between factors such as race/ethnicity and income, as well as the choice of surgical procedures and postoperative complications 51 .…”
Section: Resultsmentioning
confidence: 99%
“…48 Vertigo/dizziness and cholesteatoma were each associated with an article under the geographic/urban-rural category. 49,50 Cholesteatoma was also associated with a comprehensive disparity article that discussed the relationship between factors such as race/ethnicity and income, as well as the choice of surgical procedures and postoperative complications. 51 52 Despite some progress within the past 30 years, this review identifies clear gaps in the literature that warrant further investigation regarding otology and health disparities.…”
Section: Neoplasmmentioning
confidence: 99%
“…This is the first study to identify children from rural Appalachia having higher incidence of cholesteatoma at time of surgery. Several studies in the United States and Australia have identified associations between rural residence and development or recurrence of cholesteatoma, 33,34 but not all patients in these studies were pediatric patients. These studies do, however, bring rural residence as a significant risk factor for development and recurrence of cholesteatoma to the forefront.…”
Section: Discussionmentioning
confidence: 99%